Progress of studies on rubber seed oil in Yunnan - Jianbai Chen; Meiyun He (Proceedings of IRRDB Conference: NR Industry: Responding to Globalization, 7-8 September 2004, Kunming International Convention & Exhibition Center, China. pp.510-513.)
Rubber seed oil can be used as both edible oil and medicine. Animal tests and clinical practices have confirmed its functions in reducing fat and fading atherosis away significantly. It was showed that the cholesterol in white rat reduced from 74.3;to 28.9;and the triglyceride from 74.6mg;to 55.2mg;; the antherosclerosistic area in rabbits aorta covered 19.9;from 38.9;; 78 patients with hyperlipemia in clinics showed their cholestrol decreased by 20.20;after treated with rubber seed oil, and their triglyceride also decreased by 37.6;. However, w-3 fatty acid, which is decisive of the functions of rubber seed oil, can be easily oxidized. By means of mico-encapsulation with natural antioxidant, its anti-oxidation stability can be improved: its oxidation stability increased as 2.7 times than liquid oil according to an oxidation experimet at 64 oC for 144 hours. Vegetal w-3 fatty acid in rubber seed can be transferred into that in poultry products by using rubber seeds as forage. There exists a vast prospect in developing rubber seed oil.
Keywords: Rubber seed oil; Yunnan